Facile synthesis of C/Sn nanocomposite anode material for Li ion batteries. (November 2014) - Molenda, M.; Chojnacka, A.; Bakierska, M.; Dziembaj, R.
Abstract : C/Sn nanocomposites were prepared in simultaneous pyrolysis and carboreduction process (700 and 800°C) of a nanometric tin oxide(IV), obtained by a modified reverse microemulsion method. The proposed method provided formation of tin nanograins encapsulated in conductive carbon layers. The obtained materials with different carbon loadings (13–26 wt-%) were characterised by X-ray diffraction (XRD), low temperature nitrogen adsorption method (N2 -BET) and transmission electron microscopy. Galvanostatic discharge/charge tests, cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) as well as electrical conductivity studies were used to characterise electrochemical properties of C/Sn nanocomposites. It was found that the electrochemical performance of C/Sn nanocomposites may be affected by carbon matrix morphology.